Pengaruh Reward, Punishment Dan Promosi Jabatan Terhadap Kinerja Pegawai Pada BKPSDM Kota Probolinggo - Rohmah, Ismiatur; Elmas, Muhammad Syarif Hidayatullah; Rahajeng, Yekti (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
The study aims to determine the effect of reward, punishment and promotion partially and the strongest influence on employee performance at the Personnel and Human Resources Development Agency (BKPSDM) of Probolinggo City.The type of research used is a quantitative approach, with variables consisting of independent variables, namely reward, punishment and promotion and the dependent variable is employee performance. The population in this study amounted to 44 and the sample used amounted to 41 employees of the Probolinggo City Personnel and Human Resources Development Agency (BKPSDM) based on certain criteria, namely State Civil Apparatus (ASN) employees and Government Employees with Work Agreements (PPK). The data sources used in this study come from primary data and secondary data, with the help of the PLS 3 application.The results of the study determined that the reward variable (X1) had a significant and positive effect on employee performance (Y). The variable punishment (X2) has a significant and positive effect on employee performance (Y). The promotion variable (X3) has no significant and positive effect on employee performance (Y). The strongest variable test shows that the reward variable (X1) has the strongest influence on employee performance (Y). Because rewards have a stronger influence on employee performance, it is the first priority in improving employee performance at the Probolinggo City Personnel and Human Resources Development Agency (BKPSDM). It is recommended to consistently maintain the existing reward system, so that employees are able to work more professionally.